Accompagnement en psychopédagogie perceptive et estime de soi: recherche qualitative et quantitative auprès d’une population de personnes accompagnées en psychopédagogie perceptive - Bouchet, Valérie (2015)
This research investigates the effects of Perceptual Psychoeducation on self-esteem and attempts to answer the following question : « To which extent and how does Perceptual Psychoeducation contribute to raising self-esteem ? » The theoratical framework used is based on four consecutive chapters which address in turn the theoretical and conceptual aspects of Perceptual Psychoeducation, a first attempt at defining the concept of ways of being and the theoretical fields of motivation and of self-esteem. This dissertation has been conducted in the posture of a practioner-researcher using a mixed method. The quantitative approach refers to the Rosenberg Self-Esteem Scale which was applied to seventeen participants before and after a series of 12 sessions. It evaluates the initial level of self-esteem of the participants and how this evolved after the sessions are concluded. The qualitative approach is inspired by phenomenology and hermeneutics and is founded on Bois’ method of anticipation-emergence. The data was collected through seventeen semi-structured interviews, followed by a multi-category classificaction analysis, a case-by-case phenomenological analysis and a transversal hermeneutic analysis. The research shows positive results with regards to the effectiveness of Perceptual Psychoeducation in raising self-esteem and brings to light elements that contribute to a better understanding of the process that the participants experience as their self-esteem improves.